A real-world data analysis on the usage of paraphenylenediamine and ammonia free hair dye - Chatterjee, Manas; Mallela, Vijaya; Bhaskar, Gaurav; T. S., Vidya; Mohod, Bhagyashree; Jaiswal, Ashok (International Journal of Research in Dermatology, 2023)
Background: Dyeing of hair for various reasons is a common practice across a broad age group. Most hair dyes available in the market contain para-phenylenediamine (PPD) and/or ammonia, which are proven skin and scalp irritants. A quest for better tolerable hair dyes has led to emergence of toluene-2, 5-diamine sulfate (TDS) and monoethanolamine (MEA), as a substitute to PPD and ammonia, respectively. Methods: This retrospective study was conducted on 35 participants from four centers across India to evaluate the efficacy, and tolerance of ammonia-free and PPD-free permanent hair dye. Results: A PPD-free and ammonia-free cream-based hair dye showed promising results. The color uptake following 35 minutes of application was 100% in 54.2% of the participants. The color retention was more than 95% in 74.3% participants after 8-10 shampoo washes. The adverse effects were noted to be markedly less with only a few cases experiencing itching. The participants' feedback obtained showed a conclusively high satisfaction rate. The Physicians' assessment of efficacy and safety recorded favorable scores. Conclusions: A TDS and MEA based cream hair color can be an effective and safe alternative to PPD and ammonia-based hair dye.